Personal Names as a Self-Identity in Intercultural Comparison Context: A Literature Review - Sabila, Zetiara Nurul; Akbar, Zarina (PROCEEDING SERIES OF PSYCHOLOGY, 2024)
Personal names are crucial for individual identity and cultural expression. They often reflect parental hopes and desires, and individuals may internalize their names as part of their self-concept. Despite their significance, people may change their names due to various reasons.This study explores the acculturation of personal names in intercultural contexts. Through a literature review using PRISMA and databases like Google Scholar, Sage Journals, JSTOR, and Science Direct, 20 articles from 2012-2022 were analyzed. The search included keywords in English and Indonesian. The analysis revealed acculturation phenomena among ethnic groups and differences in personal name structures across cultures. Personal names are shaped by historical and cultural factors, and they can contribute to personal development by fostering connections with family and significant others, as well as facilitating acculturation in intercultural environments. This research highlights the influence of personal names on cross-cultural adaptation and identity construction. It underscores the importance of cultural context in understanding the meaning and significance of name.
Keywords: Intercultural Comparison; Personal Names; Self-identity